Clinicians' implicit and explicit attitudes about the legitimacy of functional neurological disorders correlate with referral decisions. Issue 2 (10th January 2023) - Begley, Roisin; Farrell, Lynn; Lyttle, Nigel; Alty, Jane; Curran, David; Williams, Stefan; Graham, Christopher D.
Abstract: Objectives: Uncertainty regarding the legitimacy of functional neurological disorder (FND) remains among some health care professionals. Despite treatment guidelines and consensus recommendations, variability in clinical practice referral decisions persists. Evidence from other conditions suggests such clinical decision making is impacted by practitioners' implicit and explicit attitudes. We aimed to identify whether health care professionals hold implicit and/or explicit attitudes about the legitimacy of FND and whether these attitudes are associated with referral decision making. Design/Methods: We included 66 health care professionals who work with people with neurological conditions: n  = 37 medical doctors, mainly neurologists ( n  = 18) and psychiatrists ( n  = 10), and n  = 29 doctoral level practitioner psychologists. Participants completed an Implicit Association Test (IAT), Implicit Relational Assessment Procedure (IRAP), a referral decision‐making vignette task and self‐report measures of explicit attitudes on FND‐legitimacy, therapeutic optimism and clinician confidence. Multiple Sclerosis (MS) was used as a comparator condition. Results: Participants self‐reported strong explicit FND‐legitimate and MS‐legitimate attitudes but demonstrated an implicit FND‐illegitimate/MS‐legitimate bias. Deeper examination provided by the IRAP data indicated pro‐FND‐legitimate attitudes, but no bias for or against FND‐illegitimate—contrasting the pro‐MS‐legitimate, anti‐MS‐illegitimate attitudes for the comparator condition. Attitudes about FND‐illegitimacy were negatively associated with likelihood of referral to physical interventions such as physiotherapy. Medical doctors had lower treatment optimism and stronger explicit attitudes that FND is illegitimate than psychologists. Conclusions: At an implicit level, clinicians are uncertain about the illegitimacy of FND, and such attitudes are associated with lower likelihood of referral to physiotherapy in particular. Improved education on FND among health care professionals is indicated.